Intermittent Cold-Blood Cardioplegia and Its Impact on Myocardial Acidosis during Coronary Bypass Surgery - Borowski, Andreas; Godehardt, Erhard; Paprotny, Gerrit; Kurt, Muhammed (The Thoracic and Cardiovascular Surgeon, 2015)
Background The purpose of the study was to assess the degree of myocardial acidosis in patients undergoing elective coronary bypass surgery, in whom intermittent cold-blood cardioplegia (ICBC) was used for myocardial protection. The results of this study are presented in comparison to those of a previous trial conducted by the same investigators, using a similar methodology, but with intermittent warm-blood cardioplegia (IWBC).Patients and Methods In 15 patients undergoing elective myocardial revascularization with ICBC for myocardial protection, metabolic changes of global ischemia indicators, lactate and pH values (measured simultaneously in coronary sinus and arterial blood) were analyzed. Lactate concentrations and pH values were measured at the beginning and the end of each cardioplegia administration, and the change-overtime analysis of the values was performed. For comparison with the results of the previous study (IWBC method) consisting of 12 patients, the analysis of variance with repeated measurements, including tests for a crossover, group, and time effect were used.Results Using the ICBC method, as compared with IWBC, no significant difference in the lactate production was observed during the first two successive cardioplegia administrations. During the third and fourth administrations, especially at the end of reperfusions, ICBC patients had a significantly lower lactate release and higher pH values, as compared with IWBC patients.Conclusion Our results suggest that ICBC has an inhibiting effect on potentially progressive myocardial acidosis during cross-clamp period.
Keywords: myocardial protection; myocardial acidosis; coronary bypass surgery